1991
DOI: 10.1111/j.1365-2796.1991.tb00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Sudden death and sleeping history among Finnish men

Abstract: An autopsy was performed in 460 consecutive cases of sudden death among 35- to 76-year-old men. The closest cohabiting individual known to each decreased subject was interviewed. Snoring history was obtained in 321 of the 371 interviews. In 86 cases there was a history of 'habitual' (almost always or always) snoring, and 88 men snored 'often'. The mean age of subjects was 55.4 years. The mean body mass index (BMI) was 26.3 kg m-2. Among the obese snorers (n = 82), apnoeas had been observed 'occasionally', 'oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(33 citation statements)
references
References 19 publications
2
29
0
2
Order By: Relevance
“…A number of reports have found associations of snoring and OSAS with coronary artery disease [22,23] and with increased risk of cardiovascular death [24], although other reports disagree [25]. Mechanisms have been postulated to account for possible increased atherogenesis in OSAS [26], and it has recently been reported that patients with coexisting CHD and OSAS are at increased risk of apnoeaassociated ischaemic events [27].…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports have found associations of snoring and OSAS with coronary artery disease [22,23] and with increased risk of cardiovascular death [24], although other reports disagree [25]. Mechanisms have been postulated to account for possible increased atherogenesis in OSAS [26], and it has recently been reported that patients with coexisting CHD and OSAS are at increased risk of apnoeaassociated ischaemic events [27].…”
Section: Discussionmentioning
confidence: 99%
“…Wykazano dobowy rytm występowania komorowych zaburzeń rytmu [712,[725][726][727][728][729] oraz większą częstość występowania SCD w porze snu (od północy do 6:00 rano).…”
Section: Rozpoznanieunclassified
“…In 1991, SEPPÄ LÄ et al [58] reported that increasing snoring severity was associated with increased risk for nocturnal sudden death, but the data were only indicative of a possible association of OSAS and nocturnal events since they were not based on polysomnographic recordings. In patients with polysomnographic diagnosis of OSAS, GAMI et al [59] found that the risk of nocturnal (between 00:00-06:00 hrs) sudden death increased with OSAS severity, whereas cardiovascular events mostly occurred between 06:00-12:00 hrs in patients with no sleep apnoea or subjects from the general population.…”
Section: Cardiovascular Morbidity and Mortalitymentioning
confidence: 99%